Penerapan Kansei Engineering untuk Menentukan Konsep Desain Kemasan Susu Cair Siap Minum - Novi Purnama Sari; Mahathir Muhammad Abrar; ibnu shiddiq pratomo; Ilhan Firza Ramadhan (Jurnal Rekayasa Sistem Industri, 2026)
Milk has become one of the fastest-selling products in the consumer goods category. The variety of packaged milk brands on the market often makes it challenging for customers to decide which milk to buy based on the appearance that aligns with their perceptions. Therefore, this study aims to develop a milk packaging design concept that meets customers’ desires and needs. The research method used is Kansei Engineering, which seeks to determine a design concept that reflects the emotional responses of customers. Another method used to support Kansei Engineering is PCA (Principal Component Analysis). The research began with a survey of 57 respondents, 47.17% of whom agreed that product development for milk is needed. Samples were collected according to the STP framework, with a total of 47 samples selected, while 30 Kansei Words were identified. The Kansei Words were then analyzed using PCA, resulting in one pair of design concepts: Informative - Uninformative. The importance of design elements in creating effective visual communication lies in their ability to support the development of design concepts for packaged liquid milk products that align with consumer perceptions. This study aims to determine design elements based on emotional connections. The approach used in the packaging development process is the Kansei Engineering method, designed to produce packaging that resonates with consumer emotions. Packaging that meets consumer perceptions is created by incorporating design elements aligned with the design concept. The correlation analysis between design elements and design concepts was conducted using a Likert scale questionnaire involving 30 respondents selected based on age and preference for liquid milk products. Morphology was determined collaboratively with expert panelists based on selected samples, forming several key factors for milk packaging through the analysis of questionnaire data. The evaluation process using the Quantification Theory Type 1 (QTT1) method identified six main design elements: transparent PET material to showcase the product content, a unique round shape, direct printing technique, integrated straw feature, classic design style, and milk illustrations featuring human elements to establish an emotional connection. A 3D mockup was created after evaluating the design elements and correlating concepts, using mind mapping and moodboards as references to produce packaging sketches that are visually appealing, specifically aligned with consumer perceptions, and relevant to target markets.